Ordinance no. 66, §§ 1-3, in DODGE CITY TIMES, Aug. 17, 1882, at 5 - (:unkn) unknown (My University, 1876)
That any person who shall in the city of Dodge City, carry concealed or otherwise about his or her person, any pistol, bowie knife, slung shot, or other dangerous or deadly weapon, except County, City, or United States officers, shall be fined in a sum not less than five nor more than one hundred dollars.
Keywords: CARRY; CARRY - CONCEALED